Innovative Biosensor Technologies in the Diagnosis of Urinary Tract Infections: A Comprehensive Literature Review - Celik, Haluk; Caf, Balim Bengisu; Cebi, Gizem (SPRINGER, 2024)
Urinary tract infections (UTIs) are prevalent bacterial infections globally, posing significant challenges due to their frequency, recurrence, and antibiotic resistance. This review delves into the advancements in UTI diagnostics over the past decade, particularly focusing on the development of biosensor technologies. The emergence of biosensors, including microfluidic, optical, electrochemical, immunosensors, and nanotechnology-based sensors, offers enhanced diagnostic accuracy, reduced healthcare costs. Despite these advancements, challenges such as technical limitations, the need for cross-population validation, and economic barriers for widespread implementation persist. The integration of artificial intelligence and smart devices in UTI diagnostics, highlighting the innovative approaches and their implications for patient care. The article envisions a future where multidisciplinary research and innovation overcome current obstacles, fully leveraging the potential of biosensor technologies to transform biosensor-based UTIs diagnosis. The ultimate goal is to achieve rapid, accurate, and non-invasive diagnostics, making healthcare more accessible and effective.
Keywords: Urinary tract infection; Biosensors; Point of care; Uropathogens; Leukocyte esterase; Nitrite; ANTIBIOTIC-RESISTANCE; MANAGEMENT; GUIDELINES; COMMUNITY; Biotechnology & Applied Microbiology; Microbiology